Commercial honey in the Philippines II. physical and chemical properties - Tilde, Aurora C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1992)
The 72 honey samples collected throughout the country were subjected to different chemical analyses.